How Common is Men's Self-Reported Sexual Interest in Prepubescent Children?. Issue 2 (12th February 2016) - Dombert, Beate; Schmidt, Alexander F.; Banse, Rainer; Briken, Peer; Hoyer, Jürgen; Neutze, Janina; Osterheider, Michael
Abstract : Consistent evidence exists for sexual interest in children in nonclinical/nonforensic male populations. However, prevalences for community men's self-reported sexual interest in children have been based on indiscriminate definitions including postpubescent individuals, age-restricted samples, and/or small convenience samples. The present research assessed men's self-reported sexual interest in children (including child prostitution and child sex tourism) on the community level and examined the link between strictly defined sexual fantasies and behaviors involving prepubescent children. In an online survey of 8, 718 German men, 4.1% reported sexual fantasies involving prepubescent children, 3.2% reported sexual offending against prepubescent children, and 0.1% reported a pedophilic sexual preference. Sexual fantasies involving prepubescent children were positively related to sexual offending against prepubescent children. Sexual interest in children was associated with subjectively perceived need for therapeutic help. In contrast to findings from forensic samples, men who reported child pornography use exclusively were identified as a subgroup differing from contact sexual offenders against prepubescent children and men who reported both child pornography use and contact sexual offenses against prepubescent children. The empirical link between child-related sexual fantasies and sexual victimization of prepubescent children and high levels of subjective distress from this inclination underscore the importance of evidence-based child sexual abuse prevention approaches in the community. Findings are discussed in terms of their relation to pedophilic disorder.